Meningkatkan Hasil Belajar Siswa Menggunakan Pembelajaran PBL Materi Asmaul Husna Kelas IV UPTD SDN 02 Koto Bangun - Amelya Delina; Yeni Husna; Yulia Ningsih; Roza Elfira; Fadhila Yusri; Adi Warman (Jurnal Pendidikan Tuntas, 2024)
This study aims to improve the learning outcomes of 4th-grade students at UPTD SDN 02 Koto Bangun on the subject of Asmaul Husna through the implementation of the Problem-Based Learning (PBL) model. The background of this research is the low learning outcomes of students in the subject of Asmaul Husna, as indicated by the students' limited understanding of the meaning and application of the values of Asmaul Husna in daily life. This classroom action research (CAR) was conducted in two cycles, with each cycle consisting of planning, action implementation, observation, and reflection phases. In the first cycle, the average student learning outcome reached 70, with a classical completeness level of 54.5%. After improvements in the second cycle, the average student learning outcome increased to 90, with a classical completeness level of 100%. Additionally, the implementation of Problem-Based Learning (PBL) also enhanced students' active participation in the learning process, particularly in terms of critical thinking, group collaboration, and problem-solving skills.